Using Free Pascal for teaching informatics - Dagienė, Valentina; Laucius, Rimgaudas (Lietuvos matematikos rinkinys, 2001)
Turbo Pascal is the main language used for teaching of algorithms in schools. However it is already outdated. Changes are needed. The paper discusses an alternative solution introducing Free Pascal into schools. The features of Free Pascal with respect to teaching of programming are analized. However the lack of acceptable interface with user remains the main obstacle to use Free Pascal for teaching purposes. The outline of a new interface designed for use in schools is presented. Problems of localization of Free Pascal and their solutions are presented as well.